Comparison of VO2max test results between the bleep test and the Harvard step test - Hanira, Hanira; Samodra, Y. Touvan Juni (Universitas Sriwijaya, 2026)
Research Objectives: VO₂max represents the maximum capacity of the body to utilize oxygen during physical activity and reflects an individual's level of cardiorespiratory fitness. VO₂max can be measured using various field tests, including the Bleep Test and the Harvard Step Test. Research Objectives: This study aimed to compare the estimated VO₂max results obtained from these two methods using the same subjects. Methods: This research employed a descriptive approach involving 18 active students from the Sports Coaching Education Program at Campus III of the Faculty of Sport Sciences, Universitas Tanjungpura, as the research sample. The instruments used were the Bleep Test and the Harvard Step Test. In the Bleep Test, participants performed a 20-meter shuttle run following the rhythm of a “bleep” sound until reaching their maximum capacity. In the Harvard Step Test, participants performed stepping exercises on a 30 cm bench for 5 minutes, preceded by a 5-minute seated rest to measure the resting pulse, followed by recovery pulse measurements every minute for three minutes. Data were analyzed descriptively and further tested using the Wilcoxon test. Results: The results showed that the average estimated VO₂max from the Bleep Test was 36.50 ml/kg/min, while the Harvard Step Test produced an average of 36.57 ml/kg/min. The Wilcoxon test indicated a significance value (2-tailed) of 0.704 (p > 0.05). Conclusion: Therefore, it can be concluded that there is no significant difference between the estimated VO₂max results obtained from the Bleep Test and the Harvard Step Test. However, the Harvard Step Test can be considered an alternative method for measuring VO₂max due to its practicality in implementation.